The views of students and academic staff regarding course contents and teaching-learning process in educational administration and supervision non-thesis master's program - Umur, Zeynep; Demirtas, Hasan (Tuba-Turkish Acad Sciences, 2018)
The aim of this study is to determine the views of students and academic staff regarding the course contents and teaching learning process in Educational Administration and Supervision non-thesis master's program. The research design of this article is a case study. The study group consists of 23 non-thesis master's program students and 5 academic staff. The data of this study was collected by the way of semi-structured interview technique. To analyse the data, content analysis was used. To conclude, a great majority of the participants have the positive views about the course contents whereas the courses' contents are not consistent/adequate with their objectives. Participants expressed that the course contents should be revised and in this process, the students' views should be taken into consideration. Most of the participants also state that the non-thesis master's program should focus on practice more and the courses should include mostly practical methods such as discussions, case study, administration and supervision while others believe that there is no need for such practices since the students work actively in the field as teachers or administrators.
Keywords: Educational administration and supervision; non-thesis master's program; training of educational administrators